Effect of coagulation bath parameters on the morphology and absorption behavior of a skin–core filament based on biomedical polyurethane and native silk fibroin microparticles. Issue 3 (February 2020) - Zhuang, Yan; Wang, Han; Wang, Linfeng; Liu, Changjun; Xu, Yuan; Zhou, Yingshan; Gu, Shaojin; Xu, Weilin; Yang, Hongjun; Liu, Keshuai
This study investigates the effect of the constituents and temperature of a coagulation bath on the morphology and water absorption behavior of a skin–core filament, which has potential application in the field of controlled drug release, based on biomedical polyurethane (BPU) and native silk fibroin microparticles (NSFPs). BPU solution and BPU/NSFP blend solution were extruded from the cortex and core channel of a coaxial double injector into a coagulation bath with different constituents and at different temperatures to form filaments. Scanning electron microscopy analysis of the skin–core filament prepared by wet-spinning revealed that the addition of ethanol decreased the exchange speed between the solvent and non-solvent and led to the formation of micropores on the surface. Meanwhile, the interface between the cortex and core became pronounced and the water absorption capability of the filament decreased with increasing ethanol concentration in the coagulation bath. The high temperature of the coagulation bath also improved the exchange speed between the solvent and non-solvent; however, its effect on the morphology of the filament was weak. Thus, a skin–core filament with different morphologies and water absorption behaviors was fabricated by controlling the constituents and temperature of the coagulation bath during the wet-spinning process. This skin–core filament has potential applications in controlled drug release.